2015
DOI: 10.1177/003335491513000503
|View full text |Cite
|
Sign up to set email alerts
|

Let's Move! Cities, Towns and Counties: Working with Local Elected Officials to Improve Community Food and Physical Activity Environments

Abstract: Services (HHS) offer their views on public health topics of the day. First Lady Michelle Obama launched the Let's Move! initiative in 2010 to address the problem of childhood obesity in the United States. For this issue's column, I asked leaders of a sub-initiative of Let's Move! that works with local elected officials to describe their experience and lessons learned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Department of Health and Human Services et al, 2010). “Let’s Move” was an extended, nationwide multi-level campaign to educate the public about the health benefits of physical activity and to encourage physical activity behavior (Bumpus, Tagtow, & Haven, 2015; McKinnon, Wiedt, Hoffnagle, & Shrimplin, 2015; Obama, 2012; U.S. Department of Health and Human Services et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Department of Health and Human Services et al, 2010). “Let’s Move” was an extended, nationwide multi-level campaign to educate the public about the health benefits of physical activity and to encourage physical activity behavior (Bumpus, Tagtow, & Haven, 2015; McKinnon, Wiedt, Hoffnagle, & Shrimplin, 2015; Obama, 2012; U.S. Department of Health and Human Services et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Torres [38] found that teachers were able to derive positive interpersonal relationships, a higher sense of belonging, and a rich teaching experience from their teaching activities, which enhanced their con dence in their self-body images and boosted their selfe cacy [39]. Teachers with high self-e cacy are not only more optimistic and positive, but also good at utilizing resources and coping with various problems and challenges in teaching with con dence of success, which leads to better work outcomes and healthier bodies [40]. Secondly, better body image can provide positive self-e cacy, protect individuals from negative psychological and emotional in uences, and rationalize the negative energy phenomena encountered by teachers in lessons and work, and the maintenance of this benign emotional state ensures good health [41], which suggests that an increase in body image contributes to an increase in the level of health, which occurs through an increase in the level of self-e cacy of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…Kuwato [43] found that teachers were able to derive positive interpersonal relationships, a higher sense of belonging, and a rich teaching experience from their teaching activities, which enhanced their confidence in their self-body images and boosted their self-efficacy [44]. Teachers with high self-efficacy are not only more optimistic and positive, but also good at utilizing resources and coping with various problems and challenges in teaching with confidence of success, which leads to better work outcomes and healthier bodies [45]. Secondly, better body image can provide positive selfefficacy, protect individuals from negative psychological and emotional influences, and rationalize the negative energy phenomena encountered by teachers in lessons and work, and the maintenance of this benign emotional state ensures good health [46], which suggests that an increase in body image contributes to an increase in the level of health, which occurs through an increase in the level of self-efficacy of the individual.…”
Section: Chain Mediating Role Of Physical Intention and Self-efficacymentioning
confidence: 99%